Respuesta :
we are given the expression of the equation of a circle that is x2 + y2 + 14x + 2y + 14 = 0. Using ocmpleting the squares:
x2 + y2 + 14x + 2y + 14 = 0(x+7)^2 + (y+1) ^2 = -14 + 49 + 1(x+7)^2 + (y+1) ^2 = 36 center thus is at (-7,-1) and the radius is equal ot square root of 36 equal to 6.
x2 + y2 + 14x + 2y + 14 = 0(x+7)^2 + (y+1) ^2 = -14 + 49 + 1(x+7)^2 + (y+1) ^2 = 36 center thus is at (-7,-1) and the radius is equal ot square root of 36 equal to 6.
The coordinates for the center of the circle and the length of the radius are (-7, -1) and 6units
Equation of a circle
The standard equation of a circle is expressed as:
x² + y² +2gx + 2fy + C= 0
where
(-g, -f) is the centre
radius = √g²+f²-C
Given the following equation
x² + y² + 14x + 2y + 14 = 0
2gx =14x
g = 7
2fy = 2y
f = 1
The centre will be at (-7, -1)
radius = √49 + 1 -14
radius = √36 = 6 units
Hence the coordinates for the center of the circle and the length of the radius are (-7, -1) and 6units
Learn more on circle here; https://brainly.com/question/26594685
#SPJ5